Should you be choosing foods by their glycemic index? (2000)
Summary This short article addresses the topic of glycemic index from a health standpoint, citing suggestions that foods with a lower glycemic index are "healthier" because they enhance satiety (feeling of fullness after eating), help fend off diabetes, help control triglyceride levels, and increase "good" cholesterol levels in the blood. The authors also present the issue as a contrversial one. It was suggested that "refined" carbohydrates that have the highest glycemic index. This is not true, as many very nutrient-dense foods have a higher glycemic index than foods commonly labelled as "empty calories." It was also suggested that glycemic index tables are inconsistent in their ratings. The fact is that the glycemic index of a food can be affected by a number of factors, including what they are eaten with, how they are physically prepared, and their ripeness. In addition, there is some variability in glycemic response from person to person. In the end, the authors suggest that more critical assessments are required before glycemic index numbers can be reported in a more organized way and before glycemic index will be considered when giving dietary advice. What the authors fail to mention is how the glycemic index of a food can affect an athlete¡¯s day of competition. Application High-performance athletes and their coaches must be cautious when reading material published for the general population. While there may appear to be inconsistency among tables listing certain food and their glycemic index, it can be easily controlled for by paying attention to the fine print. Simply put, one must read the details of the foods listed. Here are a few critical questions can help control for inconsistency among tables: What is the serving size of the food? Is it ripe or under-ripe? Is it mashed or whole? Is it plain or with a condiment? While the glycemic index of foods may not factor into the dietary advice offered by major health-promoting organizations, it has become a key ingredient in prescribing nutrition for high athletic performance. Due to their sharp effect in elevating blood sugar levels, foods with a high glycemic index have been recommended immediately post-exercise to optimize glycogen replenishment. On the other hand, it is recommended that these high-glycemic-index foods be avoided if an athlete has less than one hour to go before competition. The sharp rise in blood sugar caused by the high glycemic index food is followed by a sharp rise in insulin, which causes glucose to be taken out o the bloodstream. This can result in a sharp decline in blood sugar, and subsequently less to rely on during performance. When is comes to glycemic index, the issue for competitive swimmers is not long-term disease development, but rather (1) the utilization of blood sugar responses to maximize carbohydrate storage during training and (2) the attenuation of blood sugar "spikes" during competition.